Development of the pictorial values recognition test: assessing middle school students’ value perceptions - Kayıran, Derya (Frontiers in Psychology, 2026)
IntroductionThe purpose of this study was to develop and validate the Pictorial Values Recognition Test (PVRT), a visual-based measurement tool designed to assess middle school students’ ability to recognize 12 values. Values education is a critical component of moral and social development; however, conventional assessment methods often fail to capture students’ perceptions of values in contextual or visual formats. This study addresses this gap by introducing a reliable and contextually grounded assessment instrument.MethodA quantitative survey design was employed. The study group consisted of 336 middle school students enrolled in public schools across different regions of Türkiye during the 2025–2026 academic year. The PVRT comprised 12 items, each depicting an illustration representing a distinct value such as justice, honesty, respect, compassion, and responsibility. Students identified the value associated with each picture. Test scores ranged from 0 to 12, categorized as low (0–4), moderate (5–8), and high (9–12) levels of value recognition.ResultsThe findings showed that 64.3% of students demonstrated a moderate level, 32.7% a high level, and 3% a low level of value recognition. The KR-20 reliability coefficient (0.87), along with acceptable item difficulty (0.58–0.82) and discrimination indices (0.38–0.55), confirmed the internal consistency and validity of the test.Discussion and conclusionThe results highlight that visual-based assessment tools can effectively facilitate students’ understanding of abstract moral and social concepts. The PVRT offers educators a valid and reliable instrument for assessing value recognition and emphasizes the pedagogical value of incorporating visual materials into values education to enhance students’ engagement and comprehension.